Evaluasi Tarif Pelayanan Badan Layanan Umum Dengan Metode Unit Cost Pada Universitas Islam Negeri Imam Bonjol Padang - Ramayani Eka Putri; Suhairi Suhairi; Nini Syofriyeni (Universitas Batanghari Jambi, 2020)
This study is an applied research which aims to calculate the unit cost per service activity output at the UIN Imam Bonjol Padang Postgraduate program using the Activity Based Costing method, and compare the results of the unit cost calculation for each of the current Imam Bonjol UIN BLU service rates and provide recommendations for evaluation of rates relevant to UIN Imam Bonjol Padang's current condition. It is hoped that this research can provide valuable input so that service rates that are relevant to the development of Imam Bonjol Padang UIN can be applied and can be one of the references for calculating service rates in order to increase the level of efficiency and effectiveness of State financial management. The research design used is quantitative descriptive method. The data used in this study are secondary data in the form of budget data and expenditure expenditures released for each service activity. The results showed that almost the entire unit cost of service in the UIN Imam Bonjol Padang Postgraduate program turned out to be higher than the applicable rate (underrated). This shows that BLU UIN Imam Bonjol Padang's service rates is no longer relevant. UIN Imam Bonjol Padang needs to evaluate service rates in order to optimize financial management, so BLU services can be further improved.